FibrilPaint to determine the length of Tau amyloids in fluids - Júlia Aragonès Pedrola; Françoise A. Dekker; Tommaso Garfagnini; Guy Mayer; Margreet B. Koopman; Menno Bergmeijer; Gobert Heesink; Iris Rots; Mireille M. A. E. Claessens; Friedrich Förster; Jeroen J. M. Hoozemans; Henrik Jensen; et al. (Proceedings of the National Academy of Sciences, 2025)
Tau aggregation into amyloid fibrils is linked to the development of neurodegenerative diseases, including Alzheimer’s disease (AD). The molecular processes driving aggregation in disease are still being uncovered, highlighting the need for innovative tools to study aggregation reactions. Here, we introduce FibrilPaint1 as a tool to measure the size of Tau amyloid fibrils in fluids, from early aggregation stages to mature fibrils. FibrilPaint1 is a 22mer peptide with exciting properties: i) FibrilPaint1 binds fibrils with nanomolar affinity; ii) it also binds to precursors, down to a size of only 4 layers; iii) it does not bind to monomers; iv) it is fluorescently labeled, which allows monitoring and localizing interactions; v) FibrilPaint1 recognizes various Tau fibrils, including patient-derived fibrils from AD, corticobasal degeneration (CBD), and frontotemporal dementia (FTD); vi) it also binds to fibrils from amyloids derived from Amyloid-β, α-synuclein, and huntingtin vii) FibrilPaint1 is selective for the amyloid state and does not have background binding to amorphous aggregates, blood serum, or cell lysate. In combination with flow-induced dispersion analysis (FIDA), a microfluidics technology, we determined the molecular size of amyloid fibrils with submicroliter sample volumes. This setup acts as a molecular ruler at layer resolution—we determined Tau fibril length from 4 to 1100 layers in solution. This is an interesting parameter for molecular studies in dementia, with potential for diagnostic applications.